The perception of the importance of the insertion of hospital dentistry in the curriculum of the dentistry course: an experience report (Research, Society and Development, 2023)
Objective: The effective oral hygiene of patients hospitalized in Intensive Care Units (ICU) are paramount, since the oral biofilm has a rapid proliferation and it is common to reduce the natural hygiene of the oral cavity. Methodology: Thus, the private institution of higher education offered to the students of the 9th period of Dentistry the Discipline of Hospital Dentistry, a discipline that aims to increase the knowledge of students about the importance of comprehensive care to patients in vulnerability. 40 places were offered to the academics, in which the activities began in September 2022 and held on Tuesdays. The students were divided into groups accompanied by a responsible professional. The practices were carried out in private hospitals that serve the capital of the state of Tocantins. Results: It was evidenced that oral hygiene is of paramount importance in all patients hospitalized in hospital beds, because they are very susceptible to external diseases, and periodontal disease is the most prevalent infectious disease of oral origin and that can cause great problems for the health of the individual. Conclusion: Given all that has been exposed, there is still some resistance to their integration into the multiprofessional team, making this a great challenge.